Potential of Organic Liquid Fertilizer from Rice Washing Water and Goat Urine on The Growth of Pak Choi (Brassica rapa L. var. Chinensis) Using Hydroponic Method - Claudia, Ellen; Ricky, Donn Richard; Tobing, Joshua H. L. (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Hydroponics, an emerging agricultural technology, allows cultivation without soil, but using nutrient-rich water instead. This is promising for future agriculture, as it can be applied in various locations and offers higher quality production results, thus increasing market competitiveness. In addition, waste materials such as rice washing water and goat urine can be reused as valuable organic fertilizers. Rice washing water, rich in nutrients such as vitamin B1, phosphorus, calcium, and nitrogen, serves as a liquid organic fertilizer that promotes superior plant growth. Goat urine, containing natural phytohormones, supports root and shoot development, making it a useful alternative to organic fertilizers. Research shows that liquid organic fertilizers are often preferred over synthetic options in hydroponic systems due to their higher bioactive compound content and environmental safety. This study focuses on the cultivation of Pak Choi (Brassica rapa var. Chinensis) using various nutrient treatments, including rice washing water, goat urine, and AB Mix, with measured concentrations ranging from 1000 to 1400 Part Per Millions (PPM). The results showed significant differences in growth among the treatment groups, with AB Mix producing the highest plant height, number of leaves, and leaf width, indicating the effectiveness of nutrient type on plant development.